Peningkatan Minat Usaha Mikro (Umkm) Jamu Kota Bengkulu Dalam Pencatatan Transaksi Keuangan - Badrudin, Redy; Trisusilo, Agung; Yuristia, Rahmi (Kreativasi : Journal of Community Empowerment, 2025)
This community service project aims to change MSMEs' perceptions of financial transaction documentation, particularly among Jamu micro-enterprises (UM) in Bengkulu City. Following the offline community service activity, there was a significant increase in interest in documenting financial transactions within Kube, a joint business group in Jamu Sumber Rejeki. Prior to the activity, the group's Gradation Index (GI) was at 100%, indicating a high level of disinterest. After the program, 80% of participants moved into the "quite interested" to "very interested" categories, with a post-test GI score of 3.55, classifying them as "interested." This reflects an increase in interest from 20% to 80%. The target GI score for success was set at 3.6, and post-test results showed an improvement from 2.6 to 3.55, indicating that the activity was "on target" or "successful."